Hubungan Budaya Kerja dan Kerjasama dengan Kinerja Tenaga Kesehatan di Seluruh Puskesmas Kota Yogyakarta - Diny Rensi Assura; Ahmad Ahid Mudayana (International Journal of Healthcare Research, 2020)
Background: One of the government's efforts to achieve health development goals is by issuing the Republic of Indonesia Minister of Health Regulation Number 75 of 2014 concerning Public Health Centers (Puskesmas). The role of the puskesmas and its network as institutions that provide health services at the first level that are directly involved with the community is very important. The Puskesmas is responsible for organizing health development in its working area. To improve the performance of the puskesmas, complete information is needed about the puskesmas, including relating to the condition of the health center and its facilities, the condition of the health center network, and the staff at the puskesmas. A work culture and good collaboration are needed to achieve organizational goals (puskesmas). The lack of optimal implementation of puskesmas policies can be characterized by a lack of cooperation, not yet socialized puskesmas programs and weak human resources in providing services. This can happen because employees do not fulfill their duties and responsibilities, so evaluation is needed in order to produce good performance. The purpose of this study is to find out the relationship between work culture and collaboration with the performance of health workers in all Yogyakarta city health centers. Research Methods: This study is an analytical study with a cross-sectional approach. The sample in this study was 159 puskesmas employees who were chosen propotively stratified random sampling. The study was conducted in April - May 2019 in all Yogyakarta City Health Centers. Data were analyzed using univariate and bivariate analysis with Correlation statistical tests. Research Results: Test of correlation statistics shows the value of p-value of work culture with a performance of 0.004 (p value <0.05). Likewise the statistic test was carried out on collaboration variables with a performance of 0,000 (p value <0.05). Conclusion: There is a significant relationship between work culture and collaboration with performance.